The effect of public communication campaigns on family communication and behaviour : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Business Studies in Communication Management at Massey University - Hopkins, Kane (Massey University, 2004)
This thesis examines how mass communicated messages from a public communication campaign affect interpersonal communication within families. It also considers how interpersonal communication among family members flows on to affect behaviours in the family. The study uses McDevitt and Chaffee's five-stage sequence of behavioural activation within families to examine two pro-environmental campaigns: the Big Clean Up and Clean Up NZ. Seven families exposed to the messages of the communication campaigns were interviewed to gain an understanding of what communication process occurred as a result of these interventions. "Downward" (parent to child), and "upward" (child to parent) flows of communication were examined. The results suggest that communication among family members has a substantial bearing on a family's behavioural response to campaign messages. However, the person who engenders the discussions also plays a major role in the success or otherwise of the communication outcomes. The campaign messages had different effects on children than they did on parents. There were no significant behaviour changes in families where the parent was the initial message receiver; however where the child provided the initial intervention behaviour changes tended to occur. While children received new information, and developed new behaviours based on the campaign messages, parents tended to have existing beliefs and patterns of behaviour endorsed. The relationship between interpersonal family communication, campaign messages and changes in behaviour has implications for communicators developing campaigns that aim to change behaviour.
Keywords: New Zealand; Mass media; Mass media and publicity; Communication in the family; Interpersonal communication